IMPLEMENTASI SASTRA ANAK DIGITAL DENGAN ILUSTRASI BERBASIS AI PADA MATERI "BERHATI-HATI DI MANA SAJA" UNTUK SISWA SEKOLAH DASAR - Amelia, Decenni; Aryanto, Sani; Nuriyanti, Risma; Safitri, Alifia (Journal of Professional Elementary Education, 2025)
This study aims to describe the implementation of digital children’s literature with artificial intelligence (AI)-based illustrations on the material “Being Careful Everywhere” for elementary school students. The material “Being Careful Everywhere” discusses how to protect oneself from danger and accidents in various places such as home, school, streets, or other public areas. The research employed a descriptive qualitative method with a direct observation approach to classroom learning activities. Data were collected through observation, interviews, and documentation, then analyzed descriptively to illustrate students’ responses and the effectiveness of the media used. The results show that digital children’s literature with AI-generated illustrations successfully captures students’ attention, enhances comprehension of the story content, and fosters the character value of caution in daily life. Moreover, the use of this interactive digital medium encourages active student engagement during the learning process. Thus, the implementation of AI-based digital children’s literature can serve as an innovative alternative in elementary language learning that emphasizes digital literacy and character education.